Exploring the trajectory of personal, moral and spiritual values of 16- to 18-year-old students taking religious studies at A level in the UK. Issue 1 (2nd January 2017) - Francis, Leslie J.; Village, Andrew; Parker, Stephen G.
Abstract: This study set out to explore the trajectory of personal, moral and spiritual values of students taking Religious Studies at A level in the UK. A sample of 150 students completed a battery of measures at the beginning of their period of A level study and again at the end. The data found no difference over this period of time in personal values (purpose in life, self-esteem, and empathy) in some moral values (concerning anti-social behaviour and concerning substance use) and in levels of religious exclusivism or frequency of private prayer. The areas in which significant differences were observed were concerned with attitude toward sex and relationships, religious pluralism, belief in life after death, and mystical orientation. Between the ages of 16 and 18 years, following two years' engagement with Religious Studies at A level, the participants became more liberal in their approach toward sex and relationships, less convinced about the truth claims of religious pluralism, less likely to adhere to traditional Christian teaching on life after death, and less open to mystical experience. They are also less certain of ever having had a religious experience, and less frequent in their practice of religious attendance.